The Aftermath of Some Variables Toward Consumer Preferences of Isotonic Drinking in Surabaya - Achmad Daengs GS; Enny Istanti; Indriana Kristiawati; Rina Dewi; Diana Zuhro; Retno Susanti (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Drinking in packaging business still has appeal for entrepreneurs, it is same as in the market, and the selling of drinks is no death business. Drinking business is promising the prat profits, because it has a large market as well, especially for a country with a population of -ccroximately 230 million people as Indonesia. (Kontan, 2nd Week, October 2009). Drinking vcrrket has increased annually, from drinking market shares in overall package of 44 trillion rupiah, isotonic drinks market has its share of USD 2.9 to 3.4 billion in 2009 and continued to rise from previous years. Mizone has ranked first in three of the Top Brand Index began in 2008 to 2010 with Pocari Sweat as the competitors. The purpose of this study is to determine the effect of (I) consumer attitudes to the advertising toward consumer attitudes to the brands, (2) consumer attitudes to the advertising toward brand image, (3) consumer attitudes towards consumer preferences, (4) brand image toward consumer preferences; (5) consumer attitudes on the brand toward brand image. The population in this study is that consumers who buy and consume Mizone, with the characteristics are minimum in high school on education and domiciled in Surabaya. The sampling technique is using accidental sampling. The analysis techniques are using Structural Equation Model (SEM) with support of AMOS 15.0 program, based on the results it was obtained that there are effect of consumer attitudes on advertising toward consumer attitude on advertising toward brands image; there are effect of consumer attitudes on advertising towards brand image; there are effect of brand images towards consumer preferences; there are effect of brand image on consumer preferences; there are effect of consumer attitudes on brand toward brand image.